2017
DOI: 10.1103/physrevb.95.241111
|View full text |Cite
|
Sign up to set email alerts
|

Static charge-density-wave order in the superconducting state of La2xBaxCuO4

Abstract: Charge density wave (CDW) correlations feature prominently in the phase diagram of the cuprates, motivating competing theories of whether fluctuating CDW correlations aid superconductivity or whether static CDW order coexists with superconductivity in inhomogeneous or spatially modulated states. Here we report Cu L-edge resonant x-ray photon correlation spectroscopy (XPCS) measurements of CDW correlations in superconducting La2−xBaxCuO4 x = 0.11. Static CDW order is shown to exist in the superconducting state … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 61 publications
(83 reference statements)
1
8
0
Order By: Relevance
“…In a statically ordered system, jFðτÞj will remain unchanged, while speckle dynamics causes it to drop as a function of the time delay. Distinct from La 2−x Ba x CuO 4 (LBCO), in which the CO is static over a timescale of at least 2 h [33,34], jFðτÞj in LSNO decays after several minutes for both CO and SO, indicating charge and spin dynamics (Fig. 3).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In a statically ordered system, jFðτÞj will remain unchanged, while speckle dynamics causes it to drop as a function of the time delay. Distinct from La 2−x Ba x CuO 4 (LBCO), in which the CO is static over a timescale of at least 2 h [33,34], jFðτÞj in LSNO decays after several minutes for both CO and SO, indicating charge and spin dynamics (Fig. 3).…”
mentioning
confidence: 99%
“…The problem has also been addressed via model Hamiltonian analysis that suggested that lattice coupling might be crucial to stabilize stripes [31,32]. The implementation of resonant x-ray photon correlation spectroscopy (XPCS) at modern lowemittance synchrotron sources opens new routes to directly probe stripe formation and dynamics [33][34][35][36].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such an approach has been used extensively to study the average CDW properties [5][6][7][8][9][29][30][31]. The very high coherent flux (10 13 photons/s) at the 23-ID-1 beam line at the National Synchrotron Light Source II opens up the possibility of observing coherent interference between the domains of a weakly scattering order parameter such as cuprate CDWs [32,33]. This was configured to produce a beam of approximately 20 µm at the sample overfilling the 10 µm pinhole in the Au mask attached to the sample (see Methods).…”
Section: Althoughmentioning
confidence: 99%
“…The existence of CDWs in high-T c oxides has been recently confirmed by various experimental methods, including direct scanning-tunnel-microscopy (STM) and x-ray diffraction ones. In particular, CDWs were revealed in holedoped La 2−xBax CuO 4 [49], YBa 2 Cu 3 O 7−δ [16,[50][51][52][53][54][55][56][57][58][59][60], Bi 2 Sr 2−xLax CuO 6+δ [61], (Bi, Pb) 2 Sr 2 CuO 6+δ [62], and Bi 2 Sr 2 CaCuO 8+δ [16,56,[63][64][65][66] cuprates, as well as in electron-doped Nd 2−x Ce x CuO 4 ones [67]. The observed CDWs have either a unidirectional (stripe-like) or a bidirectional (checkerboard-like) structure.…”
Section: Introductionmentioning
confidence: 99%